A General Self-Sacrifice Template Strategy to 3D Heteroatom-Doped Macroporous Carbon for High-Performance Potassium-Ion Hybrid Capacitors - Li, Junwei; Hu, Xiang; Zhong, Guobao; Liu, Yangjie; Ji, Yaxin; Chen, Junxiang; Wen, Zhenhai (Nano-Micro Letters, 2021)
Potassium-ion hybrid capacitors (PIHCs) tactfully combining capacitor-type cathode with battery-type anode have recently attracted increasing attentions due to their advantages of decent energy density, high power density, and low cost; the mismatches of capacity and kinetics between capacitor-type cathode and battery-type anode in PIHCs yet hinder their overall performance output. Herein, based on prediction of density functional theory calculations, we find Se/N co-doped porous carbon is a promising candidate for K+ storage and thus develop a simple and universal self-sacrifice template method to fabricate Se and N co-doped three-dimensional (3D) macroporous carbon (Se/N-3DMpC), which features favorable properties of connective hierarchical pores, expanded interlayer structure, and rich activity site for boosting pseudocapacitive activity and kinetics toward K+ storage anode and enhancing capacitance performance for the reversible anion adsorption/desorption cathode. As expected, the as-assembled PIHCs full cell with a working voltage as high as 4.0 V delivers a high energy density of 186 Wh kg−1 and a power output of 8100 W kg−1 as well as excellent long service life. The proof-of-concept PIHCs with excellent performance open a new avenue for the development and application of high-performance hybrid capacitors. Highlights: 1 A newly versatile self-sacrifice method to fabricate selenium and nitrogen co-doped 3D macroporous carbon was developed. 2 The K+ storage mechanism of Se and N active sites was deeply studied by systematic electrochemical characterization combined with theoretical calculations. 3 The assembled K-ion hybrid capacitor possesses high energy/power densities and excellent cycling stability for practical applications.